Hyperoxemia During Cardiac Surgery Is Associated With Postoperative Pulmonary Complications. (2nd March 2023) - Douin, David J.; Pattee, Jack; Scott, Benjamin; Fernandez-Bustamante, Ana; Prin, Meghan; Eckle, Tobias; Ginde, Adit A.; Clendenen, Nathan
Abstract : OBJECTIVES: The use of hyperoxemia during cardiac surgery remains controversial. We hypothesized that intraoperative hyperoxemia during cardiac surgery is associated with an increased risk of postoperative pulmonary complications. DESIGN: Retrospective cohort study. SETTING: We analyzed intraoperative data from five hospitals within the Multicenter Perioperative Outcomes Group between January 1, 2014, and December 31, 2019. We assessed intraoperative oxygenation of adult patients undergoing cardiac surgery with cardiopulmonary bypass (CPB). Hyperoxemia pre and post CPB was quantified as the area under the curve (AUC) of Fio 2 above 0.21 in minutes when the corresponding peripheral oxygen saturation was greater than 92% measured by pulse oximetry. We quantified hyperoxemia during CPB as the AUC of Pao 2 greater than 200 mm Hg measured by arterial blood gas. We analyzed the association of hyperoxemia during all phases of cardiac surgery with the frequency of postoperative pulmonary complications within 30 days, including acute respiratory insufficiency or failure, acute respiratory distress syndrome, need for reintubation, and pneumonia. PATIENTS: Twenty-one thousand six hundred thirty-two cardiac surgical patients. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: During 21, 632 distinct cardiac surgery cases, 96.4% of patients spent at least 1 minute in hyperoxemia (99.1% pre-CPB, 98.5% intra-CPB, and 96.4% post-CPB). Increasing exposure to hyperoxemia was associated with an increased risk of postoperative pulmonary complications throughout three distinct surgical periods. During CPB, increasing exposure to hyperoxemia was associated with an increased odds of developing postoperative pulmonary complications ( p < 0.001) in a linear manner. Hyperoxemia before CPB ( p < 0.001) and after CPB ( p = 0.02) were associated with increased odds of developing postoperative pulmonary complications in a U-shaped relationship. CONCLUSIONS: Hyperoxemia occurs almost universally during cardiac surgery. Exposure to hyperoxemia assessed continuously as an AUC during the intraoperative period, but particularly during CPB, was associated with an increased incidence of postoperative pulmonary complications.